TO THE QUESTION OF THE NATURE AND ESSENCE OF SOCIAL ENTREPRENEURSHIP - L. Kot (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This paper is analyzed the main approaches to the definition of social entrepreneurship, the main differences between traditional entrepreneurship, social entrepreneurship and philanthropy, as well as differences in social entrepreneurship and socially responsible business. Investigated the main areas of social entrepreneurship and found that social entrepreneurship can be represented in almost all economic sectors, such as health, social care, retail and more. Analyzed of foreign experience financial support social entrepreneurship, the role and importance of social entrepreneurship in Ukraine.